Growth of Pseudomonas weihenstephanensis, Pseudomonas proteolytica and Pseudomonas sp. in raw milk: Impact of residual heat-stable enzyme activity on stability of UHT milk during shelf-life. (August 2016) - Stoeckel, Marina; Lidolt, Melanie; Achberger, Veronika; Glück, Claudia; Krewinkel, Manuel; Stressler, Timo; von Neubeck, Mario; Wenning, Mareike; Scherer, Siegfried; Fischer, Lutz; Hinrichs, Jörg
Abstract: One of the reasons for spoilage of UHT milk during shelf-life is the presence of residual proteolytic activity produced from Pseudomonas spp. during storage of raw milk. The aim of this study was to describe the product defects occurring in indirectly heated UHT milk during shelf-life, and to establish a correlation between proteolytic activity and onset of product spoilage. UHT milk was produced from raw milk incubated with different Pseudomonas strains, and examined over four months during storage at 20 °C. Inactivation kinetics of the peptidases were determined. In UHT milk, product defects occurred in the order: bitterness – particles – creaming – sediment – gelation in all the samples containing peptidases (apparent enzyme activity ≥ 0.03 pkat mL −1 ). A linear correlation was found between proteolytic activity and onset of product defects, apart from onset of gelation.